2020
DOI: 10.1021/acsnano.0c04295
|View full text |Cite
|
Sign up to set email alerts
|

Laser-Induced Tar-Mediated Sintering of Metals and Refractory Carbides in Air

Abstract: Refractory Metals and their carbides possess extraordinary chemical and temperature resilience and exceptional mechanical strength. Yet, they are notoriously difficult to employ in additive manufacturing, due to the high temperatures needed for processing. State of the art approaches to manufacture these materials generally require either a high-energy laser or electron beam as well as ventilation to protect the metal powder from combustion. Here, we present a versatile manufacturing process that utilizes tar … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 10 publications
(22 citation statements)
references
References 37 publications
0
22
0
Order By: Relevance
“…Compared with furnace annealing, laser ablation or laser annealing can reach much higher local temperatures (thousands of degrees Kelvin), 47 with faster temperature ramping 48 and also enhanced spatial control and resolution. 49,50 Laser annealing has been applied on polymeric substrates to produce carbon materials with controllable properties such as porosity, crystallinity, and conductivity (Figures 2C-2E). Lin et al demonstrated laser-induced graphene (LIG) on commercial polyimide in 2014 (Figure 2C); thereafter, many works have employed laser annealing as a simple and facile method to pattern graphene on polymeric materials including polymer films, cloth, wood, and even bread.…”
Section: Achieving Extreme Tunability In Hcmsmentioning
confidence: 99%
“…Compared with furnace annealing, laser ablation or laser annealing can reach much higher local temperatures (thousands of degrees Kelvin), 47 with faster temperature ramping 48 and also enhanced spatial control and resolution. 49,50 Laser annealing has been applied on polymeric substrates to produce carbon materials with controllable properties such as porosity, crystallinity, and conductivity (Figures 2C-2E). Lin et al demonstrated laser-induced graphene (LIG) on commercial polyimide in 2014 (Figure 2C); thereafter, many works have employed laser annealing as a simple and facile method to pattern graphene on polymeric materials including polymer films, cloth, wood, and even bread.…”
Section: Achieving Extreme Tunability In Hcmsmentioning
confidence: 99%
“…Reproduced with permission from Ref. [34], © American Chemical Society 2020. (e) Schematic illustration of the fabrication and formation process of LIG on Kevlar textiles.…”
Section: Lig Fabrications With Various Conditions and Its Electrical Propertymentioning
confidence: 99%
“…Very recently, tar was employed as both IR absorber and antioxidant binder for laser-assisted fabrication of thin metal films and metal carbides as shown in Fig. 1(d) [34]. Here, the carbon solid solubilities and formation energies of metal carbides are two critical factors that determine the formation of carbides.…”
Section: Lig Fabrications With Various Conditions and Its Electrical Propertymentioning
confidence: 99%
“…As-deposited films are carbonized and graphitized at high temperature in air via laser ablation. 16,26,27 The results show that DECS 19 with intermediate VR o (1.71%) and aromatic content shows the highest amount of graphitic structure after laser annealing, while the most mature DECS 21 (VR o 5.19%) and least mature lignite coal DECS 25 (VR o 0.23%) show rare graphitization reflected by the absence of a 2D Raman peak. 28 Sheet resistances of the laser-annealed coals increase following the descending order of coal graphitization, and the lowest sheet resistance of lased bituminous (DECS 19) is ∼30 ohm sq −1 .…”
Section: Introductionmentioning
confidence: 99%
“…9,10 Through advanced chemistry and materials processing, coal-derived functional materials have been developed including graphene oxide, 11 carbon quantum dots, 12 and carbon nanotubes, 13 which have been applied in photovoltaics, 14 energy storage devices, 15 and sensors (Table S1). 16,17 Beyond coal-derived materials, the thin film electronics that can be manufactured in a continuous (i.e., roll-to-roll) method are desired for scalable applications of coal feedstocks. 18 Therefore, a deeper understanding and nanoscale control of coal graphitization, including manipulation of electronic, magnetic, and structural properties, will amplify the potential of these nontraditional routes of coal commercialization by enabling the design and ordering of functional units at the molecular level.…”
Section: Introductionmentioning
confidence: 99%